Tingkat Suku Bunga, Brand Image Dan Kepercayaan Terhadap Penyaluran Kredit Di Pt. Bank Mandiri (Persero) Tbk Cabang Mandiraja Kabupaten Banjarnegara - Siti Maesaroh; Asih Suciati (Medikonis, 2019)
ABSTRACT Lending at PT. Bank Mandiri (Persero) Tbk Branch Mandiraja has fluctuations every year. Based on data, amount of lending in 2016 of 413 customers. In 2017 decreased to 386 customers. And in 2018 an increase of 462 customers. The occurrence of fluctuations is caused by several factors, including interest rates, brand image and trust. This study aims to analyze the influence of interest rates, brand image and trust in lending at PT. Bank Mandiri (Persero) Tbk Branch Mandiraja Banjarnegara regency. This study used a questionnaire with 82 respondents as total sample. The sampling method used is probability sampling. The analytical method used in this research was multiple linier regression analysis. The result showed that the interest rate variable had a negative and not significant effect on lending. The brand image variable had a positive and not significant effect on lending. The variable of trust had a positive and significant effect on lending. Based on the result of the R square test showed that interest rate, brand image and trust simultaneously affect the lending by 38,8%. Meanwhile, the remaining 61,2% show that the on lending variables is influente by other variable not includein this research.